Foundations of Economic Sociology - Montgomery, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is intended primarily for graduate students, though undergraduates may enroll in exceptional cases with permission of the instructor. The course is quite demanding, both in terms of the amount of weekly reading and the intellectual difficulty of some of the material. It is designed to provide students specializing in economic sociology with a stronger understanding and better appreciation of economic perspectives. Other economic sociology courses offered at UW provide a more substantive exploration of economic institutions at the micro/meso level (Sociology 652, The Sociology of Economic Institutions) and the macro level (Sociology 918, The Sociology of Comparative Capitalisms).